Reductions in malaria in pregnancy and adverse birth outcomes following indoor residual spraying of insecticide in Uganda. (December 2016) - Muhindo, Mary; Kakuru, Abel; Natureeba, Paul; Awori, Patricia; Olwoch, Peter; Ategeka, John; Nayebare, Patience; Clark, Tamara; Muehlenbachs, Atis; Roh, Michelle; Mpeka, Betty; Greenhouse, Bryan; et al.
Abstract Background Indoor residual spraying of insecticide (IRS) is a key intervention for reducing the burden of malaria in Africa. However, data on the impact of IRS on malaria in pregnancy and birth outcomes is limited. Methods An observational study was conducted within a trial of intermittent preventive therapy during pregnancy in Tororo, Uganda. Women were enrolled at 12–20 weeks of gestation between June and October 2014, provided with insecticide-treated bed nets, and followed through delivery. From December 2014 to February 2015, carbamate-containing IRS was implemented in Tororo district for the first time. Exact spray dates were collected for each household. The exposure of interest was the proportion of time during a woman's pregnancy under protection of IRS, with three categories of protection defined: no IRS protection, >0–20 % IRS protection, and 20–43 % IRS protection. Outcomes assessed included malaria incidence and parasite prevalence during pregnancy, placental malaria, low birth weight (LBW), pre-term delivery, and fetal/neonatal deaths. Results Of 289 women followed, 134 had no IRS protection during pregnancy, 90 had >0–20 % IRS protection, and 65 had >20–43 % protection. During pregnancy, malaria incidence (0.49 vs 0.10 episodes ppy, P = 0.02) and parasite prevalence (20.0 vs 8.9 %, P < 0.001) were both significantly lower after IRS. At the time of delivery, the prevalence of placental parasitaemia was significantly higher in women with no IRS protection (16.8 %) compared to women with 0–20 % (1.1 %, P = 0.001) or >20–43 % IRS protection (1.6 %, P = 0.006). Compared to women with no IRS protection, those with >20–43 % IRS protection had a lower risk of LBW (20.9 vs 3.1 %, P = 0.002), pre-term birth (17.2 vs 1.5 %, P = 0.006), and fetal/neonatal deaths (7.5 vs 0 %, P = 0.03). Conclusion In this setting, IRS was temporally associated with lower malaria parasite prevalence during pregnancy and at delivery, and improved birth outcomes. IRS may represent an important tool for combating malaria in pregnancy and for improving birth outcomes in malaria-endemic settings. Trial Registration Current Controlled Trials Identifier NCT02163447